Joining Technologies 2016
DOI: 10.5772/64158
|View full text |Cite
|
Sign up to set email alerts
|

Gas Tungsten Arc Welding with Synchronized Magnetic Oscillation

Abstract: The search for improvements in mechanized/automated welding techniques has been intense due to skilled labour shortage. In this line, the combination of operational modes (polarity and/or metal transfer mode) within a process has gained attention, since it expands the adjustability of the arc energy. By combining this feature with arc motion, the arc energy delivered to the workpiece can be optimally distributed. Therefore, this work exploits the synchronization between arc magnetic oscillation and gas tungste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In addition, a relatively small arc deflection may be noticed even during the base period. Although this may be related to a lower magnetic field density during the recorded events, an alternate possible factor is the shorter arc length immediately after restarting [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a relatively small arc deflection may be noticed even during the base period. Although this may be related to a lower magnetic field density during the recorded events, an alternate possible factor is the shorter arc length immediately after restarting [22].…”
Section: Resultsmentioning
confidence: 99%
“…Larquer et al [22] developed a model considering that the arc deflection is hindered by the plasma jet. This gas jet is caused by the unbalance of magnetic forces in regions of the arc close to the electrode and the base metal and its strength (is) proportional to the arc length and the welding current squared [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of segregation and pores, as well as the grain refinement in the weld, are the additional benefits of EMS [4,6,9,14,32,33]. The author's previous study [8] showed that EMS could make the grain boundaries less tortuous and the transformed austenite smaller in the HAZs.…”
Section: Discussionmentioning
confidence: 99%
“…The welding parameters employed could alter the microstructure-related properties such as the mechanical properites and corrosion resistance of welds [3]. Consequently, electromagnetic force in various forms has been applied to stabilize welding arcs and reduce welding defects, as a means to improve the quality of the welds by gas tungsten arc welding (GTAW) and plasma arc welding (PAW) processes [2,[4][5][6]. The mechanical properties and corrosion resistance of weldments were improved as well [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%